La evaluación del cuidado de enfermería: un compromiso disciplinar (2009)
ABSTRACT: to reflect on the evaluation of nursing care, to assist in the management of care from the disciplinary language evolved from the questions and needs of nursing professionals for the implementation of a Quality System of care, and to analyze my interaction with students of Management in the School of Nursing seeking proposals for the evaluation of nursing care. It forms part of a reading of the context of care within the health services, which requires skills from being disciplined for the solution of problems of care and the search for evidence in decision making. It also explores the nature of care and proposes from the inputs to establish a systemic approach for evaluating the structure of care processes and outcomes that determine their quality and relevance.